Techniques for Studying Materials, Raman Spectroscopy
En este conjunto de animaciones se explica la espectroscopa̕ Raman, la regla de exclusin̤ mutua, resolucin̤ espectral y las interacciones de luz con una molčula. Comprende los siguientes elementos: Interactions of light with a moleculeThe rule of mutual exclusionInteractive illustration of spectral resolutionThe light path in a Raman spectrometerRaman spectroscopy: exercise